CHANGES IN RURAL WOMEN’S MOVEMENT RELATED TO POLAND’S ACCESSION TO THE EUROPEAN UNION - Żak, Mirella (Acta Scientiarum Polonorum. Oeconomia, 2011)
Both the accession of Poland to the EU in 2004 and pre-accession period had a positive influence on changes that occurred in countryside. They particularly concern the movement of rural women, who undertake volunteer activity by implementing projects financed by the EU funds for the behave of women and local communities. At the same time they cooperate with local authorities. However, the rural women’s emancipation proceeds differently in comparison with women living in cities and towns. While being rather conservative in moral sphere, rural women are aware of social changes and perceive possibilities of personal development. Voluntary work constitutes an additional occupation for them. The fact that women’s organizations became independent is the most important change in the rural women’s movement over the last decade.